Food and drink consumption among 1–5-year-old Los Angeles County children from households receiving dual SNAP and WIC v. only WIC benefits - Liu, Jane; Kuo, Tony; Jiang, Lu; Robles, Brenda; Whaley, Shannon E (Public health nutrition, 2017)
The Supplemental Nutrition Assistance Program (SNAP) and the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) are two of the more well-known food assistance programmes in the USA. The current study describes food consumption patterns of children aged 1-5 years living in households dually enrolled in these two programmes v. households enrolled only in WIC. Food consumption and SNAP participation were assessed using data from the 2014 Survey of Los Angeles County (LAC) WIC Participants and the Follow-Up Survey of the same households that were also SNAP beneficiaries. Telephone interviews were conducted with WIC parents regarding each child's (i.e. beneficiary's) food consumption patterns. Follow-up interviews were conducted with those who reported receiving SNAP. Multivariable regression analyses were performed to assess the relationships between food and beverage consumption and dual v. single food assistance programme participation. LAC, California. Children of WIC-enrolled households in LAC during 2014 (n 3248). This included a sub-sample of dual WIC- and SNAP-enrolled households (n 1295). Survey participants were the beneficiaries' parents. Children from dually enrolled households consumed 1·03 (P<0·05) and 1·04 (P<0·01) more servings of fruits and vegetables daily respectively, 1·07 more sugar-sweetened beverages daily (P<0·001) and ate sweets/sweetened foods 1·04 more times daily (P<0·001) than children from households participating only in WIC. Results suggest that SNAP+WIC enrolment is associated with increased consumption of both healthy foods and foods containing minimal nutritional value. Complementary nutrition education efforts across the two programmes may help beneficiaries maximize healthful food purchases with SNAP dollars.